Transformasi Pendidikan Islam: Memenuhi Hak Anak dalam Era Digital - Muhammad Ilham Jaya Kesuma; M.Izzad Khairi Yazdi; Nadhifa Arufah Chafshah; Erlina; Umi Hijriyah (An Naba, 2024)
This study discusses the transformation of Islamic education in fulfilling children's rights in the digital era, with a special emphasis on the rights to education, protection, and involvement of children. This study uses a qualitative methodology based on literature and investigates research and policies on technology, education, and children's rights. The results show that digital technology brings many benefits, such as more efficient information delivery, more dynamic teacher-student interactions, and increased accessibility of learning. However, there are also major challenges, such as the digital divide, lack of technological literacy among educators and students, and threats to children's safety while in the digital environment. This study shows how important it is to incorporate technology into the curriculum, create inclusive policies, and raise digital awareness based on Islamic values in Islamic education. Technology-based curriculum innovation, active participation of children in learning, and strengthening digital literacy for all stakeholders are all ways that Islamic education can change. Collaboration between Islamic educational institutions and technology providers, as well as policies that support digital inclusion and protection of children, are some of the potential futures. In this paper, conceptual and practical foundations are provided to make Islamic education more relevant and responsive in the digital era.